2017
DOI: 10.1111/dom.12942
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of saxagliptin compared with acarbose in Chinese patients with type 2 diabetes mellitus uncontrolled on metformin monotherapy: Results of a Phase IV open‐label randomized controlled study (the SMART study)

Abstract: NCT02243176, clinicaltrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 31 publications
1
33
0
1
Order By: Relevance
“…Drugs such as Acarbose act by inhibiting α-amylase and α-glucosidases and are used in the management of T2DM. Unfortunately, this drug is expensive which is a limitation to the therapeutic treatment of T2DM in low- and middle-income countries and there is evidence showing that long-term intervention with Acarbose results in gastrointestinal side effects (flatulence occurring in ≥1/10 patients, and diarrhoea and GI and abdominal pain in ≥1/100 to <1/10 patients) [ 22 , 23 ]. For these reasons, there is still a need for new therapeutic interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Drugs such as Acarbose act by inhibiting α-amylase and α-glucosidases and are used in the management of T2DM. Unfortunately, this drug is expensive which is a limitation to the therapeutic treatment of T2DM in low- and middle-income countries and there is evidence showing that long-term intervention with Acarbose results in gastrointestinal side effects (flatulence occurring in ≥1/10 patients, and diarrhoea and GI and abdominal pain in ≥1/100 to <1/10 patients) [ 22 , 23 ]. For these reasons, there is still a need for new therapeutic interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that saxagliptin therapy in Asian patients is well tolerated in treatment‐naive patients, in combination with metformin, and in combination with other oral glucose‐lowering agents . A potential benefit of using a DPP‐4 inhibitor as add‐on therapy over other antidiabetes agents is that the activity of this class of drugs on insulin secretion is glucose‐dependent, and DPP‐4 inhibitors are therefore associated with a low risk of hypoglycaemia .…”
Section: Discussionmentioning
confidence: 99%
“…Asian patients is well tolerated in treatment-naive patients, 6 in combination with metformin, 7,13,14 and in combination with other oral glucose-lowering agents. 15,16 A potential benefit of using a DPP-4…”
Section: Previous Studies Have Demonstrated That Saxagliptin Therapy Inmentioning
confidence: 99%
“…Alogliptin is the most weight neutral DDP-4 inhibitor and associated with a weight change of −0.9 to +0.7 kg. 97 100 Conversely, sitagliptin, saxagliptin and linagliptin are associated with modest weight losses ranging from 0.1 to −2.6, 100 103 2.1 to 0.5 100 , 103 105 and 2.1 to 0.6 kg, 90 , 100 , 106 , 107 respectively. Acarbose, an α-glucosidase inhibitor, is limited in its use due to gastrointestinal side effects, but is associated with modest weight loss of 0.4–2.8 kg.…”
Section: Antidepressantsmentioning
confidence: 99%
“…Acarbose, an α-glucosidase inhibitor, is limited in its use due to gastrointestinal side effects, but is associated with modest weight loss of 0.4–2.8 kg. 5 , 77 , 87 , 105 …”
Section: Antidepressantsmentioning
confidence: 99%